Marsilio Ficino as Reader of Plotinus: The 'Enneads' Commentary - Gersh, Stephen, (History of Metaphysics: Ancient, Medieval, Modern ;, 2024)
This book represents the first ever systematic philosophical study of Marsilio Ficino's Commentary on Plotinus' 'Enneads' (first published in Florence, 1492), this work of Ficino being arguably as definitive for the Florentine thinker's later work as the Platonic Theology was for his earlier. Publication of the present study uniquely illuminates the extent to which Plotinus had always been the crucial influence over Ficino's revolutionary projects of introducing Platonic thought based on original Greek sources to western Europe, correcting certain features of late medieval and Renaissance Aristotelianism, and laying the foundations of a new Christian Platonism. The study can be read both as an independent introduction to Ficino's later philosophy and as the complement to the first modern edition and translation of the Commentary on the 'Enneads' itself also by Stephen Gersh ( I Tatti Renaissance Library , 2017-).